Processing of diffusion MR images of the brain: from crossing fibres to distributed tractography - Sotiropoulos, Stamatios N. (2010)
Diffusion-weighted (DW) magnetic resonance imaging allows the quantification of water diffusion within tissue. Due to the hindrance of water molecules by the various tissue compartments, probing for the diffusive properties of a region can provide information on the underlying structure. This is particularly useful for the human brain, whose anatomy is complex. Diffusion imaging provides currently the only tool to study the brain connectivity and organization non-invasively and in-vivo, through a group of methods, commonly referred to as tractography methods.